Effects of different sponsorship disclosure message types on consumers' trust and attitudes. Issue 1 (15th August 2020) - Pfeuffer, Alexander; Huh, Jisu
Abstract: Addressing the problem of increasing sponsored eWOM and diverse and confusing disclosure practices, this study examined the effects of different types of sponsorship disclosure messages on (1) consumers' trust in the sponsored product reviewer and (2) attitudes toward the reviewer and the sponsoring brand. An online experiment revealed several key effects of sponsorship disclosure and disclosure message types. Overall, sponsorship disclosure messages generated lower consumer trust in the reviewer and attitudinal responses. In terms of the effects of different types of disclosed commercial gain, reviews disclosing the receipt of a free product were perceived to be equally acceptable as reviews without sponsorship disclosure. Disclosure revealing that the reviewer received payment or a sales commission led to lower trust in a reviewer, and disclosure of a sales commission generated more negative attitude toward the sponsoring brand. The disclosure message type effects on attitude were mediated by trust.